Can Schools Buy Success in College Football? Coach Compensation, Expenditures and Performance - McDonald, Paul Mirabile; Witte, Mark David (Journal of Research in Educational Sciences; Vol 5 No 1 (2014): JRES, Volume V, Issue 1(7), 2014, 2014)
Using unique data of Football Bowl Subdivision college football games, we examine the determinants of coach compensation, football expenses and performance. We find that coach compensation is highly related to the coach’s past success. Additionally, coach pay is higher when the institution has a larger fan base and the program has achieved a higher profit in the previous year. Football expenses are likewise determined by institutional characteristics such as the fan base, past profitability and historical success. Results suggest that coach compensation has no measurable impact on performance. A coach’s past success may impact their salary but their salary has no significant impact on future success. Though, an additional, aspirational increase in spending of $1 million on the football program can improve the probability of winning any particular game by 3.5% to 7.0%. Thus, the budget of an administrator is a better predictor of future performance than the coach’s salary.